Model, instruments, and unity index and their impact on the unity policy - Abdul Rahim, Habibah; Alias, Bity Salwana; Ishak, Mohd Radzi; Zainudin, Zaida Nor (Scientific Research Publishing, 2019)
The discussion on unity has never come to an end. To date, various actions have been taken to strengthen unity. Yet the direction of strengthening unity is still blurry whereas the measurement of unity in Malaysia remains a challenge. In 2014, the Education Planning and Research Division (EPRD), Ministry of Education Malaysia (MOE) through Unity Level Measurement Survey led to the success of developing instruments to produce an index as well as in developing a Unity Model of Teachers and Student. The index can be interpreted to determine unity level of students and teachers. To date, KPM has succeeded in producing the unity index for 2014, 2016, and 2018. Besides sharing KPM’s achievements, this paper discussed on student unity index for 2014, 2016, and 2018 as well as the impact of the index on the unity initiative under the Malaysia Education Blueprint (PPPM) 2013-2025. The unity index and model are also referred by the other Divisions at MOE to streamline the Student Integration Plan for Unity, developing Guideline Book to Strengthen Unity through Islamic Education Subjects and Moral Education, developing Guidelines for Unity Practices in Schools, Conducting Yearly Unity Practice Inspections at Schools, and developing Unity Roadmap in Education. Various parties also refer to these models and instruments in conducting their studies on unity.